COMPUTED TOMOGRAPHY FINDINGS IN ACUTE PANCREATITIS - Hadi, Noor ul; Nawab, Kalsoom; Amin, Ayesha (Journal of Postgraduate Medical Institute, 2011)
Objective: To determine the role of computed tomography in the diagnosis of acute pancreatitis and to determine the presence of its complications. Material and Methods: A prospective descriptive study was carried out at Radiology Department, Hayatabad Medical Complex Peshawar from January 2006 to June 2007.180 consecutive patients with suspected or known acute pancreatitis underwent contrast enhanced helical computed tomography (CT) scan. Scans were observed for pancreatic size, its outlines and other associated complications. The pancreatic findings on CT were classified into five categories on the basis of Balthazar score; A: normal B: pancreatic enlargement alone C: inflammation confined to the pancreatic and peripancreatic fats D: one peripancreatic fluid collection E: two or more fluid collections. Results: Out of 180 patients, 110(61%) were males and 70(39%) were females. The pancreatic CT findings were grade A in 30 patients (17%); grade B in 34 (19%);grade C in 55 (30%); grade D in 29 (16%); and grade E in 32 (18%)patients. 25 pseudocysts were detected while abscesses were seen only in three patients. Adjacent organ involvement such as spleen and left kidney was noted in 6 cases. Conclusion: Abdominal CT scan plays an important role in the quick and accurate diagnosis and staging of pancreatitis. CT can assess the degree of pancreatic involvement by the disease process and enables detection of complications.